METHODOLOGY FOR IMPROVING THE TECHNICAL AND TACTICAL TRAINING OF NATIONAL WRESTLERS - Khamidzhonov Abdunazar Usubzhan ugli (Research Focus International Scientific Journal, 2023)
this article presents the scientific methodological foundations of improving the technique and tactics of national wrestlers